Jump to content
Sign in to follow this  

Roots of polynomials in an arithmetic sequence proof problem

Recommended Posts

Prove that if the roots of x^3 - ax^2 + bx -c=0 are in an arithmetic sequence
then 2a^3 -9ab + 27c=0.
Hence find x : x^3 - 12x^2 +39x -28=0
I tried making equation with the sum and products of the terms as well as making an equation with the sequence but had no luck so far.

Share this post


Link to post
Share on other sites
Guest

My initial guess is that you should write the cubic as: (x-p)(x-q)(x-r)=x^3 -ax^2 + bx -c =0

Then you can express a, b and c in terms of the zeros and possibly vice versa.

As they are in an arithmetic sequence: p-q=q-r -> 2q - p - r = 0.

Maybe you can find a way to substitute p,q and r and confirm the 2a^3 - 9ab - 27c=0

I'm not sure about it but maybe it helps

Share this post


Link to post
Share on other sites

I actually managed to do this question! I was so intrigued by it that I had to solve it through until an answer came up. I used sum/product of roots to solve it, so maybe you just had a mistake in your method. Bear with me through the notation here.

Let your roots be e-f, e, e+f (they are in AS).

Given your cubic equation of x^3-ax^2+bx-c=0, we can make several equations.

a = sum of roots taken one at a time = (e-f)+e+(e+f) = 3e

b = sum of roots taken two at a time = e(e-f)+e(e+f)+(e-f)(e+f)=3e^2-f^2

c = sum of roots taken three at a time = e(e-f)(e+f) = e(e^2-f^2)

Therefore, that means we can substitute into 2a^3-9ab+27c=0, and prove that LHS=RHS=0.

LHS = 2a^3-9ab+27c = 2(3e)^3-9(3e)(3e^2-f^2)+27(e(e^2-f^2))

= 54e^3 - 81e^3 + 27ef^2 + 27e^3-27ef^2

= 0 = RHS

That means that for these particular circumstances, 2a^3-9ab+27c=0 is true.

Now onto the second part of the question - solving x^3-12x^2+39x-28=0.

We can compare this with the form x^3-ax^2+bx-c=0. Here, a=12, b=39, c=28.

We know that a = 3e. Therefore, a=12=3e --> e=4

We know that c = e(e^2-f^2). Substituting e=4, c=28=4(16-f^2). Solving gives you f = 3.

As the roots are e-f, e, e+f, that menas that the roots of x^3-12x^2+39x-28=0 are x=1,4,7. Which can be confirmed using a GDC.

Hope that helped! Perhaps there is a quicker/more elegant way to do this, but if you do everything correctly, this should get you there. This question is actually good revision for me, as I have been woefully negligent in practising maths questions lately.

  • Like 3

Share this post


Link to post
Share on other sites

I actually managed to do this question! I was so intrigued by it that I had to solve it through until an answer came up. I used sum/product of roots to solve it, so maybe you just had a mistake in your method. Bear with me through the notation here.

Let your roots be e-f, e, e+f (they are in AS).

Given your cubic equation of x^3-ax^2+bx-c=0, we can make several equations.

a = sum of roots taken one at a time = (e-f)+e+(e+f) = 3e

b = sum of roots taken two at a time = e(e-f)+e(e+f)+(e-f)(e+f)=3e^2-f^2

c = sum of roots taken three at a time = e(e-f)(e+f) = e(e^2-f^2)

Therefore, that means we can substitute into 2a^3-9ab+27c=0, and prove that LHS=RHS=0.

LHS = 2a^3-9ab+27c = 2(3e)^3-9(3e)(3e^2-f^2)+27(e(e^2-f^2))

= 54e^3 - 81e^3 + 27ef^2 + 27e^3-27ef^2

= 0 = RHS

That means that for these particular circumstances, 2a^3-9ab+27c=0 is true.

Now onto the second part of the question - solving x^3-12x^2+39x-28=0.

We can compare this with the form x^3-ax^2+bx-c=0. Here, a=12, b=39, c=28.

We know that a = 3e. Therefore, a=12=3e --> e=4

We know that c = e(e^2-f^2). Substituting e=4, c=28=4(16-f^2). Solving gives you f = 3.

As the roots are e-f, e, e+f, that menas that the roots of x^3-12x^2+39x-28=0 are x=1,4,7. Which can be confirmed using a GDC.

Hope that helped! Perhaps there is a quicker/more elegant way to do this, but if you do everything correctly, this should get you there. This question is actually good revision for me, as I have been woefully negligent in practising maths questions lately.

Thanks!

I solved it yesterday after posting( mine was a little more complex but it gave the same results ). I left it here hoping for a quicker solution and this is just what I wanted.

Maybe there is an even quicker solution but when it comes to polynomials the proof is always long compared to some others problems IMO

Share this post


Link to post
Share on other sites

Create an account or sign in to comment

You need to be a member in order to leave a comment

Create an account

Sign up for a new account in our community. It's easy!

Register a new account

Sign in

Already have an account? Sign in here.

Sign In Now
Sign in to follow this  

×

Important Information

We have placed cookies on your device to help make this website better. You can adjust your cookie settings, otherwise we'll assume you're okay to continue.